Передумови становлення та розвитку вищої освіти у Європі - Мартіросян, Леся Анатоліївна; Martirosian, Lesia A. (Східноєвропейський національний університет ім.Лесі Українки, 2013)
У статті висвітлено передумови становлення та розвитку вищої освіти у Європі. The author of the article analyses the historical process of higher education emergence in Europe. The activity of different establishments that present higher level of education in the epoch of Antiquity and Medievalism is presented in the given article. A special attention is paid to the educative teaching and scientific activity of such educative establishments as gymnasiums, philosophic and rhetorical schools, centers of scientific activity and Byzantine higher schools. It was determined that modem classical universities and technical universities take their origin in the Rome empire and were developed in Byzantine and medieval Europe.
Precondition of the Development of Higher Education in Europe
Keywords: освіта; гімнасії; гімнасії; філософські школи; риторичні школи; університет; наукова діяльність; вища світа; європейський освітній простір; educatioh; gymnasium; philosophic and rhetorical schools; scientific activity; European educational expanse